2012
DOI: 10.1016/j.ajpath.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Skeletal Muscle on the Regulation of Liver:Body Mass and Liver Regeneration

Abstract: The relationship between liver and body mass is exemplified by the precision with which the liver:body mass ratio is restored after partial hepatic resection. Nevertheless, the compartments, against which liver mass is so exquisitely regulated, currently remain undefined. In the studies reported here, we investigated the role of skeletal muscle mass in the regulation of liver:body mass ratio and liver regeneration via the analysis of myostatin-null mice, in which skeletal muscle is hypertrophied. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It was reported that knocking out of myostatin results in comparable absolute liver weight, lower liver/body weight ratio, and decreased ALT activity of the liver (18). We found that liver mass and liver/body weight ratios are not increased in proportion to skeletal muscle mass in Compact mice; therefore, we aimed to assess whether ALT activity in proportion to body weight is also reduced similarly to myostatin knockout animals.…”
Section: Body Composition Of Compact Micementioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that knocking out of myostatin results in comparable absolute liver weight, lower liver/body weight ratio, and decreased ALT activity of the liver (18). We found that liver mass and liver/body weight ratios are not increased in proportion to skeletal muscle mass in Compact mice; therefore, we aimed to assess whether ALT activity in proportion to body weight is also reduced similarly to myostatin knockout animals.…”
Section: Body Composition Of Compact Micementioning
confidence: 99%
“…The Compact mutation and genetic background affected glucose tolerance and insulin sensitivity; therefore, we evaluated glucose uptake in different tissues with known insulin responsiveness using small-animal PET/MRI imaging. By the quantitative analysis of decay-corrected 18 FDG-PET images, we found significant differences in the SUV mean of the selected organs 50 min after tracer injection (Fig. 6).…”
Section: Balb/c Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7,[30][31][32] Some mice were treated with SAHA (or vehicle control) as previously described. <0.001 increased no effect Csk 0.05 <0.001 no effect no effect Igf1 0.05 0.009 no effect no effect Ddah1 0.09 <0.001 no effect no effect Lcn2 <0.001 0.003 increased no effect Dpm1 0.09 0.02 no effect no effect Myc 0.03 0.02 increased decreased Ern1 0.08 0.1 no effect increased Nlrp12 <0.001 0.002 increased no effect Foxo1 0.03 0.2 no effect no effect Pik3r1 0.03 0.2 increased no effect Foxo3* 0.06 0.04 decreased increased Prox1 <0.001 <0.001 no effect no effect Gclc 0.08 <0.001 no effect no effect Sik1 <0.001 <0.001 increased no effect H2-K1 0.03 <0.001 increased no effect Tcf7l2 0.09 0.06 no effect no effect Jmy 0.05 0.1 no effect increased Ndfip1 <0.001 0.03 decreased no effect Nr3c1 0.006 <0.001 decreased no effect* Sesn2 0.002 0.003 no effect no effect Tmbim6 0.02 0.006 decreased no effect Traf4 0.09 0.009 no effect increased 1 Identified using DAVID bioinformatics database 2 as described in text; 3 Listed by "Official gene symbol" (genes in bold are over-connected in the interactome analysis in Figures 2A-B All experiments were approved by the Washington University Animal Studies Committee and conducted in accordance with institutional guidelines and the criteria outlined in the "Guide for Care and Use of Laboratory Animals" (NIH publication 86-23 revised 1985).…”
Section: Methodsmentioning
confidence: 99%